Belief, attitude and critical understanding. A systematic review of social justice in Service‐Learning experiences. (12th July 2022) - Compare, Christian; Albanesi, Cinzia
Abstract: This systematic review examined the role of Service‐Learning experiences promoted by higher education institutions to strengthen the achievement of social justice outcomes among youth. We screened and coded studies following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA). Of the 555 articles found in the database search, 47 peer‐reviewed studies were included in the final sample. Social justice construct, together with research location, participants, target community and outcomes, were coded. Results show effects of Service‐Learning experiences on (a) fostering significant improvement of students' social justice beliefs, (b) stimulating significant changes in students' attitudes with respect to the development of altruistic behaviours and their commitment to social justice, and (c) increasing students' critical understanding by sparking questioning processes related to personal assumptions of inequalities. This systematic review provides insights into the strengths and challenges of implementing social justice‐oriented Service‐Learning experiences.